Employee stock options and the impact on firm performance after the global financial crisis in 2008. - Tan, Sing Nan. (2012)
The purpose of this article is to examine the change in issuance of employee stock options (ESOP) in response to the Global Financial Crisis in 2008, and the effect of using this measure on firm performance. Results are based on financial data collected for a sample of 344 large to medium-sized companies listed on the New York Stock Exchange that had increased ESOP, juxtaposed against data for 338 large to medium-sized companies that had reduced ESOP or did not issue any ESOP entirely. Findings showed that companies generally granted more ESOP after the recent recession, and this increase was found to be positively associated with a rise in firm productivity and financial performance. Thus, it can be conclusively stated that ESOP can aid post-recession recovery. Prior to this study, little research had examined the trend in ESOP issuance immediately after a recession and its possible impact on firm recovery. The scale of the Global Financial Crisis and its far-reaching effects across multiple industries presented a unique opportunity to conduct such a study.